Polyphenols as Tyrosine Kinase Inhibitors for the Treatment of Metastatic Cancers: Current and Future Perspective - Saad Hussain; Qasim Mahmood Alhadidi (Indonesian Journal of Pharmacy, 2022)
Cancer is the world's biggest cause of death as a whole. The higher cancer mortality rate is related to metastasis, which is a major stumbling block in cancer treatment. Polyphenols are a diverse set of antioxidant-rich natural compounds that are often used in cancer treatments as chemopreventives and adjuvants. To find publications that highlight the topic of this review paper, a thorough literature search was conducted in several electronic databases such as PubMed Central, Google Scholar, Scopus, and Medline. Many signaling pathways are involved in the metastatic cascade, including the tyrosine kinase pathway. Tyrosine kinases are a group of enzymes involved in the control of cancer spread. Polyphenols' true role in cancer metastasis remains unappreciated, despite a large body of research proving their antimetastatic effects. As a result, the current work lays out cancer metastasis signaling pathways, stressing the importance of tyrosine kinases in the metastatic process. Polyphenols can suppress tyrosine kinase activity, which contributes to their antimetastatic characteristics. The importance of polyphenols in preventing cancer metastasis by interfering with the tyrosine kinase signaling cascade is highlighted in this work, which could lead to the development of future antimetastatic drugs.